2022
DOI: 10.3389/fcell.2021.823546
|View full text |Cite
|
Sign up to set email alerts
|

Application and Progress of Raman Spectroscopy in Male Reproductive System

Abstract: Raman spectroscopy is a fast-developing, unmarked, non-invasive, non-destructive technique which allows for real-time scanning and sampling of biological samples in situ, reflecting the subtle biochemical composition alterations of tissues and cells through the variations of spectra. It has great potential to identify pathological tissue and provide intraoperative assistance in clinic. Raman spectroscopy has made many exciting achievements in the study of male reproductive system. In this review, we summarized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…[47] Moreover, another study also showed that using Raman spectroscopy, increased markers of OSI in the seminal plasma metabolome of men with unexplained infertility were detected (Zhang et al, 2015). [48] However, this method had also limitations. Especially the resolution of obtained spectra causes the bands often overlap.…”
Section: Machine Learning Models Based On Raman Spectra Classifymentioning
confidence: 99%
“…[47] Moreover, another study also showed that using Raman spectroscopy, increased markers of OSI in the seminal plasma metabolome of men with unexplained infertility were detected (Zhang et al, 2015). [48] However, this method had also limitations. Especially the resolution of obtained spectra causes the bands often overlap.…”
Section: Machine Learning Models Based On Raman Spectra Classifymentioning
confidence: 99%
“…Raman spectroscopy, or Raman scattering, is based on the interaction between a laser beam and a sample and enables the measurement of the vibrational energy of the tested sample. Thus, the set of Raman shifts that correspond to the vibrational energies are recorded, and they are called the Raman spectrum, which is considered a "biochemical fingerprint" of the tested sample [10][11][12][13]. The combination of Raman spectroscopy and machine learning has become a powerful diagnostic tool that has shown great potential in the medical field in recent years [14].…”
Section: Introductionmentioning
confidence: 99%